The influence of arts engagement on the mental health of isolated college students during the COVID-19 outbreak in China - Chen, Yanying; Zeng, Xue; Tao, Lijian; Chen, Junxiang; Wang, Yuhui (Frontiers in Public Health, 2022)
Objectives：The COVID-19 pandemic significantly impacted the mental health of college students. This study aimed to investigate the buffering effect of arts engagement on anxiety and resilience in college students during the COVID-19 pandemic. Study design：A cross-sectional study. Methods：The data were collected via an online survey during a wave of SARS-CoV-2 infections in Shanghai (March 15 to April 15). In total, 2453 college students throughout China reported general anxiety symptom levels (according to the GAD-7), resilience (according to the Connor-Davidson Resilience Scale), frequency of receptive arts engagement in the previous year, exposure to risk situations, and behavioral changes due to the pandemic. Results：During the current stage of the pandemic, 43.7% of college students suffered from varying degrees of anxiety, and 2.6% showed severe anxiety. Gender and learning stage were not associated with anxiety. Hierarchical regression analysis showed that the decision to return to school, the degree of exposure to COVID-19, and the frequency of accepting art participation and resilience could significantly predict the anxiety level of college students. Gender, study stage, behavioral changes arising from COVID-19, and exposure to COVID-19 significantly predict the resilience level of college students. Musical activity and reading had statistically significant effects on anxiety scores (p < 0.001). Digital arts, musical activity, and reading statistically affected resilience scores (p < 0.01). Conclusions Arts engagement appears to help students cope with mental health problems and those at risk. Policymakers should encourage college students to participate in art activities, especially in the context of social distancing.